The effects of trust mediator and education level moderator on adoption of Islamic banking system in Tajikistan - Ashurov, Sharofiddin; Othman, Anwar Hasan Abdullah (Voprosy Ekonomiki N.P, 2019)
High levels of trust and education are essential factors in the banking industry, especially for an Islamic banking system that is Shariah-based. Therefore, this paper seeks to measure the impact of trust and educational level on the decision as to whether to adopt Islamic banking in Tajikistan for business activities. The data of the study was developed based on a survey and collected through a distributed questionnaire. A total of 408 respondents were obtained from 14 banks in Tajikistan. The study adopted the Structural Equation Modeling (SEM) approach (using AMOS version 22.00) to examine these relationships. The findings of the study revealed that relative advantage and product knowledge were statistically significant in influencing perceived trust in Islamic banks, while perceived trust in Islamic banks had a directly significant impact on the adoption of the Islamic banking system in Tajikistan. Also it found that perceived trust plays a mediating role between awareness and adoption of the Islamic Banking system. This indicates that banks’ customers in Tajikistan have more trust in, and prefer dealing with, a banking system that is Shariah-based in line with their Islamic beliefs. In addition, the findings revealed that educational level plays a significant moderating role between the awareness of Islamic banks and the adoption of the Islamic banking system. The findings of the study therefore may assist policy makers to improve the current banking industry, by focusing on the Islamic banking system that would be able to restore trust and create interest among the Muslim majority population as they believe in the Islamic banking system, which will contribute positively to economic growth.